PENGARUH KEPEMILKAN INSTITUSIONAL, PROPORSI DEWAN KOMISARIS INDEPENDEN, KOMITE AUDIT TERHADAP EARNING MANAGEMENT PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2011-2013 - Candra, Bob; Zulbahridar, Zulbahridar; Surya, Raja Adri Satriawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to prove the influence of institutional ownership, the proportion of independent board, and audit committe againts earning management. This is study an empirical study on the effect of the influence of institutional ownership, the proportion of independent board, audit committee againts earning management in the mining company listed on the indonesian stock exchange period 2011-2013. This study was conducted on mining companies listed on the indonesian stock exchange in period 2011-2013. Total sampel of 16 firms or 48 observations were selected through purposive sampling method. The data used are secondary data consisting of the data earning management, institutional ownership, the proportion of independent board, and audit committee. Hypothesis testing is done using multiple regretions. The result showed that audit committee and the proportion of independent board no effect on earning management, while the institutional owner effect earning management.Keywords: earning management, institusional owner, the proportion independent board, and audit committee.